Folic acid-mediated re-shuttling of ferritin receptor specificity towards a selective delivery of highly cytotoxic nickel(II) coordination compounds - Tesarova, Barbora; Charousova, Marketa; Dostalova, Simona; Bienko, Alina; Kopel, Pavel; Kruszyński, Rafał; Hynek, David; Michalek, Petr; Eckschlager, Tomas; Stiborova, Marie; Adam, Vojtech; Heger, Zbynek (International journal of biological macromolecules, 2019)
Metal-based coordination compounds, including the well-known cytostatic drug cisplatin, are widely used in the anticancer therapy. Generally, they exhibit high cytotoxicity not only towards malignant cells, but also towards non-malignant cells, which represents main problem of their clinical use. Herein, we describe the synthesis, characterization and biological testing of three trinuclear nickel(II) coordination compounds. Central nickel atoms are bridged by trithiocyanurate anion and coordinated by triamine and bis-benzimidazoles, respectively. To delineate a potential usage in anticancer therapy, we encapsulated the most cytotoxic complex into biomacromolecular protein cage apoferritin (FRT), forming FRTNi. FRT encapsulation markedly decreased the hemotoxicity of free Ni compounds. Despite FRTNi can be internalized through passive targeting by enhanced permeability and retention effect, we further introduced active targeting utilizing folate receptor (FR) via folic acid (FA)-modified FRT (FRTNiFA). Using breast cancer cell lines T-47D (FR+), MCF-7 (FR-) and non-malignant mammary gland derived cell line HBL-100 (FR-), we show pronounced FR-dependent internalization of FRTNiFA. Overall, we demonstrate that the FRT macromolecular nanocarrier provides a very low off-target toxicity, which could enable the use of highly toxic Ni compounds in cancer nanomedicine.
Keywords: Humans; nádorové buněčné linie; pohyb buněk; Endocytosis; ferritiny; Iron-Binding Proteins; endocytóza; lidé; Clone Cells; proliferace buněk; Ligands; proteiny vázající železo; nikl; ligandy; Biocompatible Materials; Ferritins; buněčné klony; Folic Acid; Apoptosis; komplexní sloučeniny; Cell Death; receptory buněčného povrchu; apoptóza; biokompatibilní materiály; Cell Proliferation; Coordination Complexes; buněčná smrt; kyselina listová; Receptors, Cell Surface; Nickel; Cell Line, Tumor; Cell Movement